Antigen Specific for Bacteria Resistant to Tetracycline - Boldur, Ida (1974)
Antisera produced against envelope fractions of tetracycline-resistant Escherichia coli and supernatant fluid of disrupted cells of tetracycline-resistant Salmonella typhi were adsorbed with the corresponding fractions of susceptible cultures. With these sera, cross-reacting antigens were demonstrated in the following fractions obtained from tetracycline-resistant strains: envelopes of E. coli, supernatant fluid of S. typhi, and envelopes and supernatant fluid of Pseudomonas aeruginosa. These antigens were not demonstrable in the corresponding fractions from tetracycline-susceptible strains.